Study of kidney morphologic and structural changes related to different ischemia times and types of clamping of the renal vascular pedicle - Angela Mazzeo; Anna Paula Weinhardt Baptista Sincos; Katia Ramos Moreira Leite; Miguel Angelo Góes Jr.; Oscar Fernando Santos dos Pavão; Oskar Grau Kaufmann (International Brazilian Journal of Urology)
ABSTRACT Purpose This study aimed to study morphological and renal structural changes in relation to different ischemic times and types of renal vascular pedicle clamping. Methods Sixteen pigs were divided into two groups (n = 8): Group AV - unilateral clamping of the renal artery and vein and Group A - unilateral clamping of the renal artery only, both with the contralateral kidney used as control. Serial biopsies were performed at 0, 10, 20, 30, 40, 50, 60, 70, 80, and 90 minutes after clamping. Results there is a correlation between the occurrence of renal damage as a function of time (p <0.001), with a higher frequency of Group A lesions for cellular alterations (vascular congestion and edema, interstitial inflammatory infiltrate, interstitial hemorrhage and cell degeneration), with the exception of in the formation of pigmented cylinders that were evidenced only in the AV Group. Conclusion the number of lesions derived from ischemia is associated with the duration of the insult, there is a significant difference between the types of clamping, and the AV Group presented a lower frequency of injuries than Group A. The safety time found for Group A was 10 minutes and for Group AV 20 minutes.